Petrography, geochemistry, and provenance of the corumbataí formation outcropping in the municipality of mineiros (go) - Montibeller, Cibele Carolina [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
In the state of Goiás, similar lithotypes to those attributed to the Corumbataí Formation occur in the state of São Paulo, although the lack of specific bibliographies about the unit in the Brazilian Midwest region, and the absence of detailed mappings in the vicinity of Serra do Caiapó (Central-Southeast of Goiás State) raise doubts as to the correlation between these outcrop areas of permian units and those found in the São Paulo domain of the Paraná Basin. Thus, this work presents mineralogical, petrographic, and geochemical characteristics of the Corumbataí Formation in the state of Goiás, and its implications of provenance, weathering, and paleoclimate, in order to provide complementary data that allow establishing correlations between the several outcropping areas of the unit along the north and east edges of the Basin. The siltstones of the municipality of Mineiros (GO) are chemically classified predominantly as wackes and arkose, and secondarily as lithoarenites and sublithoarenites, with high textural maturity, and variable chemical maturity, generated by sediments mainly from quartz sedimentary rocks, with lower contributions of felsic and mafic igneous rocks. Apparently, these sediments suffered little effect from sedimentary recycling, advocating a closer proximity to the source areas, subjected to varying degrees of weathering, which suggests a mixing of various sources in the generation of sediments that gave rise to the unit, and there is a predominance of classification of sources as derived from tectonically active regions or continental island arches.
Petrografia, geoquímica e proveniência da Formação Corumbataí aflorante no município de Mineiros (GO)
Keywords: Brazilian Midwest geology; Lithogeochemistry; Paraná Basin; Passa Dois Group; Permian